Optimal age to start teaching a foreign language (with an emphasis on Teaching English as a Foreign Language) considering cultural factors: A research synthesis - Vidā Rahiminezhād; Mohammadrezā Anāni Sarāb (فصلنامه نوآوری‌های آموزشی, 2022)
The optimal age to start teaching a foreign language is one of the most challenging topics in foreign language education, especially when the role of culture in such education is discussed. The aim of this research was to identify the optimal age range for foreign language education (focusing on English) and considering the cultural factors. The method adopted in this study was synthesis of the related studies. In the first stage of research synthesis, through electronic search of the databases over a time period starting from 1961 to 2020, 81 sources were identified as the research population. Subsequently, through two round of purposeful sampling 19 studies were selected for the next stage. In the second stage, the selected researches were analyzed using the physiological analysis tables. The results of the analysis were entered into the synthesis stage, which has two sub-stages of aggregate and combined synthesis. In the synthesis stage, the data were integrated with the purpose of coding, which resulted in open, axial and selective codes. The selective codes included the intercultural competence, cultural-critical awareness, early learning of second language culture, and the time required for the formation of the first and second language culture. The findings indicated that the majority of researchers whose studies were reviewed conceded that the optimal age range to start teaching a foreign language considering cultural factors is the age range below 12 years preferably young children of 3 to 5 years old. The results of the present study could be used by foreign language education policy makers.